Tuning metal support interactions enhances the activity and durability of TiO2-supported Pt nanocatalysts. (10th January 2017) - Hsieh, Bing-Jen; Tsai, Meng-Che; Pan, Chun-Jern; Su, Wei-Nien; Rick, John; Chou, Hung-Lung; Lee, Jyh-Fu; Hwang, Bing-Joe
Graphical abstract: Highlights: The coverage of TiOx on Pt can be modified by thermal and fluoric acid treatments. Strong metal support interaction (SMSI) can be testified by electrochemical method. For the first time, the SMSI effect is observed at 200 °C with supporting TEM images. Increased activity and stability are attributed to stronger SMSI. This tunable approach is valid for other oxide supported catalysts, e.g. Pt/Nb-TiO2 . Abstract: A facile approach to enhance catalytic activity and durability of TiO2 -supported Pt nanocatalysts by tuning strong metal support interaction (SMSI) is investigated in this work. No need for a high temperature treatment, the strong metal-support interaction (SMSI) in TiO2 -supported Pt can be induced at 200° C by H2 reduction. Moreover, electrochemical methods (methanol oxidation reaction and cyclic voltammetry) are first reported ever to be effective characterization tools for the coverage state caused by SMSI. In addition, the SMSI has also been confirmed by X-ray photoelectron spectroscopy, X-ray absorption spectroscopy, and Transmission Electron Microscopy. It is found that the encapsulation of TiO2-x species on the surface Pt clusters was induced and modified by thermal reduction and fluoric acid treatment. The catalytic activity and durability of the TiO2 -supported Pt nanocatalysts are strongly dependent of the state of SMSI. The proposed SMSI-tunable approach to enhance the ORR activity and stability is also proved applicable to Pt/Ti0.9 Nb0.1 O2 nanocatalysts. We believe that the reported approach paves the way for manipulating the activity and stability of other TiO2 -supported metal nanocatalysts. Furthermore, the suggested electrochemical methods offer facile and effective ways to verify the presence of coverage state before combining with other physical analysis.